2007
DOI: 10.1590/s0101-20612007000100014
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do processamento na contaminação de cana-de-açúcar e derivados por hidrocarbonetos policíclicos aromáticos

Abstract: 76 ResumoOs hidrocarbonetos policíclicos aromáticos (HPAs) são compostos formados a partir da queima incompleta de material orgânico e compreendem uma importante classe de contaminantes ambientais, muitos deles comprovadamente carcinogênicos. No presente estudo, amostras de caldo de cana-de-açúcar colhida verde e cana colhida queimada e produtos intermediários e finais do processo de obtenção do açúcar de cana foram analisados para a presença de 5 HPAs carcinogênicos. Para a análise dos compostos foi utilizada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
(24 reference statements)
0
4
0
14
Order By: Relevance
“…Ensiling is recognized to depress feed intake of forages and other fermentation end products than those measured in this study such as ammonia-N, biogenic amines and alcohols, which are typical of poor-fermented silages (untreated burned silages showed low DM recovery), and can reduce silage palatability, and hence feed intake (Buchanan-Smith, 1990;Charmley, 2001). Moreover, a small quantity of compounds formed by burning of sugarcane such as polycyclic aromatic hydrocarbons might remain on the standing forages (Tfouni, Vitorino, & Toledo, 2007) and could contribute to decreased palatability of forage. In this regard, even though the current study showed that burned sugarcane can be saved by ensiling, burned silage should be used in low amount in the feedlot diets, so that DMI is not depressed.…”
Section: Feed Intake Growth Performance and Carcass Characteristicsmentioning
confidence: 74%
“…Ensiling is recognized to depress feed intake of forages and other fermentation end products than those measured in this study such as ammonia-N, biogenic amines and alcohols, which are typical of poor-fermented silages (untreated burned silages showed low DM recovery), and can reduce silage palatability, and hence feed intake (Buchanan-Smith, 1990;Charmley, 2001). Moreover, a small quantity of compounds formed by burning of sugarcane such as polycyclic aromatic hydrocarbons might remain on the standing forages (Tfouni, Vitorino, & Toledo, 2007) and could contribute to decreased palatability of forage. In this regard, even though the current study showed that burned sugarcane can be saved by ensiling, burned silage should be used in low amount in the feedlot diets, so that DMI is not depressed.…”
Section: Feed Intake Growth Performance and Carcass Characteristicsmentioning
confidence: 74%
“…A floculação pode ser obt ida por uma mudança de pH do meio, utilizando-se reagentes químicos e pelo aquecimento (LEITÃO, 1973). A clarificação do caldo envolve basicamente as etapas de sulfitação (contato contracorrente do caldo e dióxido de enxofre), calagem (o caldo recebe leite de cal), e/ou adição de compostos poliméricos de cadeia longa, sendo o caldo aquecido e ocorrendo a decantação e, consequentemente, a formação do caldo clarificado que segue para a etapa de Sacarose, suas propriedades e os novos edulcorantes concentração (TFOUNI et al, 2007).…”
Section: O Processo De Obtenção Da Sacaroseunclassified
“…A clarificação do caldo de cana-de-açúcar ocorre através da coagulação, floculação e precipitação dos coloides e substâncias corantes, eliminadas por decantação e filtração, ou seja, forma-se um precipitado insolúvel que absorve e arrasta as impurezas do caldo. A floculação pode ser obtida por uma mudança de pH do meio, utilizando-se reagentes químicos e pelo aquecimento (LEITÃO, 1973 (TFOUNI et al, 2007). No Brasil predominam dois modelos de clarificação: defecação simples (emprega apenas cal e aquecimento para obtenção de açúcar bruto), e sulfo-defecação (antes do tratamento com cal e aquecimento, ocorre adição de SO 2 ao caldo para fabricação de açúcar cristal branco) (KOBLITZ, 1998).…”
Section: Clarificação Do Caldo De Cana-de-açúcarunclassified